Heat pumps and their role in decarbonising heating sector: A comprehensive review - Ankita Singh Gaur; Desta Z. Fitiwi; John A. Curtis (The Economic and Social Research Institute (ESRI), 2019)
Addressing the growing concerns of climate change necessitates the decarbonisation of energy sectors globally. The heating sector is the largest energy end-use, accounting for almost half of the total energy consumption in most countries. This paper presents an extensive review of previous works on several aspects of heat pumps, including their role in the decarbonisation of the heating sector. In addition, we cover themes related to the recent technological advances of heat pumps as well as their roles in terms of adding flexibility to renewable-rich systems and carbon abatement. We also identify challenges and barriers for a significant uptake of heat pumps in various markets. Generally, as the share of renewables in the energy mix increases, heat pumps can play a role in addressing a multitude of problems induced by climate change. However, economic, regulatory, structural and infrastructural barriers exist, which may hinder heat pump integration rate.
Keywords: 330; Decarbonization; GHG emissions; heat pumps; heating sector; flexibility; renewable energy sources